Uncertainty assessment of a permanent long-range terrestrial laser scanning system for the quantification of snow dynamics on Hintereisferner (Austria) - Voordendag, Annelies; Goger, Brigitta; Klug, Christoph; Prinz, Rainer; Rutzinger, Martin; Sauter, Tobias; Kaser, Georg (Frontiers in Earth Science, 2023)
A permanently installed terrestrial laser scanner (TLS) helps to investigate surface changes at high spatio-temporal resolution. Previous studies show that annual and seasonal glacier volume and subsequently mass balance can be measured by TLSs. This study systematically identifies and quantifies uncertainties and their sources of the permanent long range TLS system at Hintereisferner glacier (Ötztal Alps, Austria) in order to assess its potential and limitations for detecting glaciologially relevant small-scale surface elevation changes, such as snow fall and redistribution events. Five uncertainty sources are analyzed: the registration method, the influence of the instrument and hardware limitations of the TLS, the effect of the atmospheric conditions on the laser beam, and the scanning geometry, as well as the uncertainty caused by the rasterization. The instrument and hardware limitations cause the largest uncertainty to the TLS data, followed by the scanning geometry and influence of varying atmospheric conditions on the laser beam respectively. The magnitude of each uncertainty source depends on the distance (range) between the TLS and the target surface, showing a strong decrease of obtained spatial resolution and a concurrent increase in uncertainty with increasing distance. An automated registration method results in an uncertainty of ±0.50 m at grids of 100 by 100 m. After post-processing, a 0.1 m vertical accuracy can be obtained allowing the detection of surface changes of respective magnitudes and especially makes it possible to quantify snow dynamics at Hintereisferner.